Negative active material, negative plate containing negative active material and lithium ion battery
By copolymer coating of silicon-based materials, the problem of silicon material's volume expansion and low conductivity during charging and discharging of lithium-ion batteries is solved, and higher cycle life, capacity retention and rate performance are achieved.
Patent Information
- Application Number
- CN202411960650.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
During the charging and discharging of lithium-ion batteries, silicon materials will undergo huge volume expansion, low conductivity and poor circulation performance, which will not meet the actual application needs.
The silicon-based material is coated with a copolymer formed by a copolymerization of a specific first monomer and a second monomer to form a cladding layer to buffer volume expansion, improve structural and chemical stability, and enhance conductivity.
It effectively buffers the volume expansion of silicon-based materials during charging and discharging, improves cycle life and capacity retention, and enhances rate performance and fast charging performance.
Smart Images

Figure BDA0005218664030000011 
Figure BDA0005218664030000021 
Figure BDA0005218664030000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material, a negative electrode sheet containing the negative electrode active material, and a lithium ion battery. Background Art
[0002] With the rapid development of mobile electronic devices, electric vehicles and grid energy storage, the development of lithium-ion batteries with high energy density, high power density, long cycle life and high safety is a research hotspot and focus in the field of energy storage today. The development of negative electrode materials with high capacity, high rate and high cycle stability is an important way to achieve this goal.
[0003] Silicon materials have attracted widespread attention due to their abundant reserves and extremely high theoretical charge capacity. However, silicon materials have problems such as huge volume expansion (greater than 300%) and inherent low conductivity during the charge and discharge process, and the lithium storage capacity of silicon materials decays rapidly during the cycle, which cannot meet the needs of practical applications. Summary of the invention
[0004] In order to solve the problems of huge volume expansion, low conductivity and poor cycle performance of existing silicon materials during charge and discharge, the present invention provides a negative electrode active material, a negative electrode sheet containing the same and a lithium ion battery.
[0005] According to a first aspect of the present invention, there is provided a negative electrode active material, the negative electrode active material comprising a silicon-based material and a coating layer disposed on the surface of the silicon-based material, the coating layer comprising a copolymer, the copolymer comprising a first monomer as shown in Formula I and a second monomer as shown in Formula II;
[0006]
[0007] X and Y independently contain at least one of an aryl group and an alkenyl group;
[0008] The Z is selected from one of —Cl, —Br, and —I.
[0009] In the negative electrode active material provided by the present invention, a copolymer formed by copolymerization of a first monomer shown in Formula I and a second monomer shown in Formula II is used to coat the silicon-based material. First, since the silicon-based material is prone to expansion during the charge and discharge process, the copolymer formed by the first monomer shown in Formula I and the second monomer shown in Formula II has good flexibility. Coating the silicon-based material with the copolymer can play a good buffering role in the volume expansion of the silicon-based material during the charge and discharge process, so that the negative electrode active material is not easy to break during the expansion process, thereby improving the cycle life and cycle capacity retention rate of the negative electrode active material in actual use. Second, coating the silicon-based material with the above copolymer can improve the structural stability and chemical stability of the negative electrode active material, thereby reducing the continuous generation of unstable SEI film on the surface of the negative electrode sheet due to silicon volume expansion. Third, since the electronic conductivity of the silicon-based material itself is low, the coating layer formed by coating the silicon-based material with the above copolymer can improve the conductivity of the negative electrode active material to a certain extent, thereby improving the rate performance of the negative electrode active material, so that the lithium ion battery using the negative electrode active material provided by the present invention has excellent fast charging performance.
[0010] Preferably, the structure of the first monomer is as shown in Formula III, and the structure of the second monomer is as shown in Formula IV;
[0011]
[0012] The first monomer shown in Formula III contains a long dodecane chain, which has good flexibility. The second monomer shown in Formula IV contains a benzene ring, which has rigidity. The copolymer formed by the copolymerization reaction of the first monomer shown in Formula III and the second monomer shown in Formula IV contains both a long dodecane chain and a benzene ring, so the copolymer has both good flexibility and rigidity. The negative electrode active material is obtained by coating the silicon-based material with the copolymer. The coating layer can not only further improve the buffering effect on the volume expansion of silicon during the charge and discharge process, but also improve the flexibility of the negative electrode sheet using the negative electrode active material, which is beneficial to reduce the risk of peeling of the negative electrode active coating containing the negative electrode active material. The above two effects extend the cycle life of the lithium ion battery using the negative electrode active material, so that the capacity retention rate of the lithium ion battery after multiple cycles of charge and discharge can still be maintained at a high level.
[0013] Preferably, the number average molecular weight of the copolymer is 4,000 to 50,000.
[0014] The number average molecular weight of the copolymer used to form the coating layer is controlled within the range of 4000 to 50000. Firstly, the bonding strength of the coating layer can be maintained within an appropriate range, which is beneficial to reduce the risk of the coating layer falling off or peeling off during multiple cycles of charge and discharge of the negative electrode active material. Secondly, the coating layer has good mechanical strength, which can improve the buffering effect of the coating layer on the volume expansion of silicon during the charge and discharge of the negative electrode active material. Thirdly, the coating layer has good uniformity and density, which can improve the cycle stability of the negative electrode active material during the charge and discharge process.
[0015] If the number average molecular weight of the copolymer used to form the coating layer is too small, the bonding strength of the coating layer will be low, the coating layer will easily fall off or peel off during the charge and discharge cycle, and the mechanical strength of the copolymer will be low; if the number average molecular weight of the copolymer used to form the coating layer is too large, the solubility of the copolymer in organic solvents will be poor, which will increase the difficulty of coating and also affect the uniformity and density of the coating layer.
[0016] Preferably, the molar ratio of the first monomer to the second monomer is 1-1.2:1.
[0017] By controlling the molar ratio of the first monomer and the second monomer in the copolymer used to form the coating layer within the above range, the coating layer made of the copolymer formed by the copolymerization reaction of the first monomer and the second monomer can have good mechanical strength and flexibility, thereby reducing the risk of cracking of the coating layer due to volume expansion of the silicon-based material during the charge and discharge process of the negative electrode active material.
[0018] If the molar ratio of the first monomer to the second monomer is too high, that is, there is too much first monomer, although the coating has good flexibility, its rigidity is poor, and the coating is prone to cracking; if the molar ratio of the first monomer to the second monomer is too low, that is, there is too little first monomer, although the coating has strong rigidity, the coating is easily affected by silicon expansion and cracking.
[0019] Preferably, the coating layer accounts for 2-8% by mass of the negative electrode active material.
[0020] Preferably, the coating layer has a thickness of 10 to 130 nm.
[0021] Controlling the mass ratio and thickness of the coating layer within the above range can further improve the lithium ion transport performance, rate performance and cycle performance of the negative electrode active material, and the coating layer has good flexibility.
[0022] If the mass proportion of the coating layer is too small and the thickness is too thin, the coating layer will easily break during multiple cycles of charge and discharge, resulting in loss of active lithium; if the mass proportion of the coating layer is too large and the thickness is too thick, the ion transport performance of the negative electrode active material will be poor, resulting in a decrease in its rate performance and cycle performance.
[0023] Preferably, the particle size D50 of the negative electrode active material is 4 to 9 μm.
[0024] Preferably, the specific surface area of the negative electrode active material is 1 to 8 m 2 / g.
[0025] Controlling the specific surface area of the negative electrode active material within the above range can improve the stability of the negative electrode active material and enable its capacity to be better utilized during the cyclic charge and discharge process.
[0026] If the specific surface area of the negative electrode active material is too small, the contact area between the negative electrode active material and the electrolyte is too small, which may cause the internal resistance of the lithium-ion battery using the negative electrode active material to be relatively high, limiting the performance of the negative electrode active material; if the specific surface area of the negative electrode active material is too large, the negative electrode active material is more likely to agglomerate during the preparation of the negative electrode sheet, making the dispersion of the material more difficult, thereby affecting the performance of the negative electrode sheet.
[0027] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned negative electrode active material, comprising the following steps:
[0028] S1. copolymerizing the first monomer and the second monomer to obtain a copolymer;
[0029] S2. preparing a copolymer solution using the copolymer;
[0030] S3. Applying the copolymer solution to the surface of the silicon-based material, and drying the copolymer solution on the surface of the silicon-based material to form a coating layer on the surface of the silicon-based material.
[0031] In this scheme, a copolymer formed by a copolymerization reaction of a first monomer and a second monomer is used to coat a silicon-based material, so that the obtained negative electrode active material has good structural stability and chemical stability, thereby improving the cycle performance and fast charging performance of a lithium-ion battery using the negative electrode active material, so that the lithium-ion battery still maintains a high capacity retention rate after multiple cycles of charge and discharge, thereby improving the cycle life of the battery.
[0032] Preferably, in S1, the above copolymer is prepared by the following steps:
[0033] S1-1. The first monomer, the second monomer, the base and the catalyst are mixed and heated under reflux under an inert gas atmosphere for 5 to 12 hours to obtain a prepolymer;
[0034] S1-2. The prepolymer is mixed with an organic solvent and an initiator, and reacted in an inert gas atmosphere at 40 to 100° C. for 3 to 12 hours to obtain a copolymer.
[0035] This scheme first utilizes the Suzuki coupling reaction to couple the first monomer and the second monomer in the presence of a base and a catalyst, and then adds an initiator to open the double bond and cause a copolymerization reaction to obtain a copolymer. The copolymer obtained by the above method has better performance. The copolymer is applied to the coating layer, which can further improve the structural stability, chemical stability, rate performance and cycle performance of the negative electrode active material.
[0036] Preferably, S1-2 includes the following operations: mixing the prepolymer with an organic solvent and an initiator and reacting them in an inert gas atmosphere at 40 to 100° C. for 3 to 12 hours to obtain a reaction solution, adding the reaction solution to a precipitation solvent to obtain a copolymer precipitate, and washing and drying to obtain a copolymer.
[0037] Preferably, in S1-2, the precipitation solvent includes at least one of propanol, isopropanol and acetone.
[0038] Preferably, in S1, the amount of the initiator used is 0.1-0.9% of the total mass of the first monomer and the second monomer.
[0039] Preferably, in S1-1, the base includes at least one of sodium carbonate, potassium carbonate, potassium phosphate and sodium bicarbonate.
[0040] Preferably, in S1-1, the catalyst includes at least one of Pd(dppf)Cl2, Pd(PPh3)4.
[0041] Preferably, in S1-2, the organic solvent includes at least one of benzene, toluene, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).
[0042] Preferably, in S1-2, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide (BPO).
[0043] Preferably, in S2, the mass fraction of the copolymer solution is 3-20%.
[0044] Preferably, S3 includes the following operations: mixing the silicon-based material and the copolymer solution and stirring at 30-80° C. for 4-10 hours to obtain a mixed solution, and spray-drying the mixed solution to obtain a negative electrode active material.
[0045] Preferably, in S3, the inlet temperature of the spray drying is 100-200°C, and the outlet temperature is 60-90°C.
[0046] Preferably, the silicon-based material includes at least one of silicon monoxide (SiO) and silicon carbon material (SiC).
[0047] Preferably, the silicon-carbon material includes a porous carbon skeleton, a silicon layer and a carbon layer, the porous carbon skeleton includes an inner layer region and an outer layer region wrapping the inner layer region, the inner layer region has a plurality of inner holes, the outer layer region has a plurality of outer holes, the silicon layer is arranged on the inner walls of the inner holes and the outer holes, and the carbon layer is arranged on the surface of the silicon layer in the outer holes, so that the silicon-carbon particles have inner pores in the inner layer region and outer pores in the outer layer region.
[0048] Preferably, among the internal pores and external pores of the silicon-carbon material, the proportion of mesopores is 42-86%, and the proportion of micropores is less than 58%, wherein the diameter of the mesopores is 3-40 nm, and the diameter of the micropores is 0.5-2 nm.
[0049] According to a third aspect of the present invention, a negative electrode sheet is provided, which includes a negative electrode collector and a negative electrode active coating arranged on the surface of the negative electrode collector, and the negative electrode active coating contains the above-mentioned negative electrode active material or the negative electrode active material prepared by the above-mentioned method for preparing the negative electrode active material.
[0050] The negative electrode active material provided by the present invention is applied to the negative electrode sheet, so that the negative electrode sheet has good flexibility, plays a certain buffering role on the volume expansion of the negative electrode active material during the charge and discharge process, reduces the expansion rate of the negative electrode sheet, and improves the cycle performance and rate performance of the negative electrode sheet.
[0051] According to a fourth aspect of the present invention, a lithium-ion battery is provided, comprising the negative electrode sheet described above.
[0052] The negative electrode active material provided by the present invention is applied to a negative electrode sheet, and the negative electrode sheet is applied to a lithium ion battery, which is beneficial to improving the cycle performance and rate performance of the lithium ion battery. DETAILED DESCRIPTION
[0053] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] A lithium ion battery is prepared by the following steps:
[0056] 1. Preparation of negative electrode
[0057] The negative electrode active material, conductive carbon black (SP), single-walled carbon nanotube (SWCNT), and binder polyacrylic acid (PAA) were mixed in a mass ratio of 80:9:1:10 and added to a solvent deionized water, and mixed evenly to prepare a negative electrode slurry with a solid content of 30%. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil to form a negative electrode active coating, and after vacuum drying and cold pressing, a negative electrode sheet was prepared;
[0058] The negative electrode active material comprises a silicon-based material and a coating layer disposed on the surface of the silicon-based material, wherein the coating layer contains a copolymer, wherein the copolymer comprises a first monomer as shown in Formula III and a second monomer as shown in Formula IV;
[0059]
[0060] The above negative electrode active material is prepared by the following steps:
[0061] S1. The first monomer and the second monomer are mixed in a molar ratio of 1:1 and added to an organic solvent THF, sodium bicarbonate and Pd(PPh3)4 are added, and the mixture is heated under reflux for reaction for 8 hours under argon protection to obtain a prepolymer solution, which is then cooled and diluted with ethyl acetate, washed with brine, dried, filtered, and concentrated to obtain a concentrate, which is added to ethyl acetate / hexane for recrystallization to obtain a prepolymer, the prepolymer is mixed with THF and azobisisobutyronitrile, and the mixture is reacted under argon protection at 70°C for 8 hours to obtain a reaction solution, the reaction solution is added to propanol to obtain a copolymer precipitate, and the copolymer having a number average molecular weight between 20,000 and 22,000 is obtained after washing and drying;
[0062] S2. The copolymer was dissolved in THF to prepare a copolymer solution having a mass fraction of 12%;
[0063] S3. Adding the silicon-based material to the copolymer solution and stirring at 50°C for 7h to obtain a mixed solution, spray drying the mixed solution to form a coating layer with a thickness of 70nm on the surface of the silicon-based material, and preparing a negative electrode active material with a particle size D50 of 6μm, wherein the mass proportion of the coating layer in the negative electrode active material is 5%, the inlet temperature of the spray drying is 150°C, and the outlet temperature is 75°C;
[0064] The silicon-based material involved in this embodiment is silicon-carbon material.
[0065] 2. Preparation of positive electrode
[0066] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1O2, conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2 and added to a solvent N-methylpyrrolidone (NMP). The mixture is evenly mixed to obtain a positive electrode slurry with a solid content of 45%. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil to form a positive electrode active coating. After vacuum drying and cold pressing, a positive electrode sheet is obtained.
[0067] 3. Preparation of Diaphragm
[0068] A polyethylene (PE) film containing a ceramic layer is used as the diaphragm.
[0069] 4. Preparation of Electrolyte
[0070] Ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 20:40:30:10 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M.
[0071] 5. Assembly of lithium-ion batteries
[0072] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is placed in an outer packaging shell, dried and injected with the above-mentioned electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0073] Example 2
[0074] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the negative electrode active material used in the negative electrode sheet is different.
[0075] The negative electrode active material used in this embodiment is prepared by the following steps:
[0076] S1. The first monomer and the second monomer are mixed in a molar ratio of 1.1:1 and added to an organic solvent THF, sodium bicarbonate and Pd(PPh3)4 are added, and the mixture is heated under reflux under argon protection for 5 hours to obtain a prepolymer solution, which is then cooled and diluted with ethyl acetate, washed with brine, dried, filtered, and concentrated to obtain a concentrate, which is added to ethyl acetate / hexane for recrystallization to obtain a prepolymer, the prepolymer is mixed with THF and azobisisobutyronitrile, and the mixture is reacted under argon protection at 40°C for 12 hours to obtain a reaction solution, the reaction solution is added to propanol to obtain a copolymer precipitate, and the copolymer having a number average molecular weight between 4000 and 6000 is obtained after washing and drying;
[0077] S2. The copolymer was dissolved in THF to prepare a copolymer solution having a mass fraction of 3%;
[0078] S3. Add the silicon-based material to the copolymer solution and stir at 30°C for 10 hours to obtain a mixed solution, spray-dry the mixed solution to form a coating layer with a thickness of 10 nm on the surface of the silicon-based material, and prepare a negative electrode active material with a particle size D50 of 4 μm, wherein the mass proportion of the coating layer in the negative electrode active material is 2%, the inlet temperature of the spray drying is 200°C, and the outlet temperature is 90°C.
[0079] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0080] Example 3
[0081] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the negative electrode active material used in the negative electrode sheet is different.
[0082] The negative electrode active material used in this embodiment is prepared by the following steps:
[0083] S1. The first monomer and the second monomer are mixed in a molar ratio of 1.2:1 and added to an organic solvent THF, sodium bicarbonate and Pd(PPh3)4 are added, and the mixture is heated under reflux under argon protection for 12 hours to obtain a prepolymer solution, which is then cooled and diluted with ethyl acetate, washed with brine, dried, filtered, and concentrated to obtain a concentrate, which is added to ethyl acetate / hexane for recrystallization to obtain a prepolymer, the prepolymer is mixed with THF and azobisisobutyronitrile, and the mixture is reacted under argon protection at 100°C for 3 hours to obtain a reaction solution, the reaction solution is added to propanol to obtain a copolymer precipitate, and the copolymer having a number average molecular weight between 48,000 and 50,000 is obtained after washing and drying;
[0084] S2. The copolymer was dissolved in THF to prepare a copolymer solution having a mass fraction of 20%;
[0085] S3. Add the silicon-based material to the copolymer solution and stir at 80°C for 4 hours to obtain a mixed solution, spray-dry the mixed solution to form a coating layer with a thickness of 130 nm on the surface of the silicon-based material, and prepare a negative electrode active material with a particle size D50 of 9 μm, wherein the mass proportion of the coating layer in the negative electrode active material is 8%, the inlet temperature of the spray drying is 100°C, and the outlet temperature is 60°C.
[0086] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0087] Example 4
[0088] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the negative electrode active material contains a different copolymer, and the first monomer used is as shown in formula V;
[0089]
[0090] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0091] Example 5
[0092] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the negative electrode active material contains a different copolymer, and the first monomer used is as shown in formula VI;
[0093]
[0094] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0095] Example 6
[0096] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the negative electrode active material contains a different copolymer, and the first monomer used is as shown in formula VII;
[0097]
[0098] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0099] Example 7
[0100] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the negative electrode active material contains a different copolymer, and the second monomer used is as shown in formula VIII;
[0101]
[0102] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0103] Example 8
[0104] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the negative electrode active material contains a different copolymer, and the second monomer used is as shown in formula IX;
[0105]
[0106] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0107] Example 9
[0108] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the negative electrode active material, the prepolymer is mixed with THF and azobisisobutyronitrile and reacted at 70° C. for 2 hours under argon protection, and the number average molecular weight of the obtained copolymer is 2000-3000.
[0109] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0110] Example 10
[0111] This embodiment provides a lithium ion battery. Compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the negative electrode active material, the prepolymer is mixed with THF and azobisisobutyronitrile and reacted under argon protection at 70° C. for 14 hours, and the number average molecular weight of the obtained copolymer is 52000-54000.
[0112] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0113] Embodiment 11
[0114] This embodiment provides a lithium-ion battery. Compared with Embodiment 1, the differences in structure are: (1) in the preparation step S2 of the negative electrode active material, the mass fraction of the copolymer solution is 1%; (2) in the preparation step S3 of the negative electrode active material, the particle size D50 of the negative electrode active material finally obtained is 2 μm, the thickness of the formed coating layer is 7 nm, and the mass fraction of the coating layer in the negative electrode active material is 1%.
[0115] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0116] Example 12
[0117] This embodiment provides a lithium-ion battery. Compared with Embodiment 1, the differences in structure are: (1) in the preparation step S2 of the negative electrode active material, the mass fraction of the copolymer solution is 25%; (2) in the preparation step S3 of the negative electrode active material, the particle size D50 of the negative electrode active material finally obtained is 12 μm, the thickness of the formed coating layer is 150 nm, and the mass fraction of the coating layer in the negative electrode active material is 12%.
[0118] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0119] Comparative Example 1
[0120] This comparative example provides a lithium ion battery. Compared with Example 1, the difference in structure is that the negative electrode active material used in the preparation process of the negative electrode sheet is a silicon-based material without a coating layer.
[0121] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0122] Comparative Example 2
[0123] This comparative example provides a lithium ion battery. Compared with Example 1, the difference in structure is that in the preparation process of the negative electrode sheet, the coating layer in the negative electrode active material used contains only the first monomer shown in Formula III, and does not contain the second monomer shown in Formula IV, that is, the silicon-based material is coated with the first monomer shown in Formula III. Specifically, a monomer solution with a mass fraction of 12% is prepared using the first monomer shown in Formula III and THF, and the silicon-based material is mixed with the monomer solution and then spray-dried to obtain the negative electrode active material.
[0124] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0125] Comparative Example 3
[0126] This comparative example provides a lithium ion battery. Compared with Example 1, the difference in structure is that in the preparation process of the negative electrode sheet, the coating layer in the negative electrode active material used contains only the second monomer shown in Formula IV, and does not contain the first monomer shown in Formula III, that is, the second monomer shown in Formula IV is used to coat the silicon-based material. Specifically, a monomer solution with a mass fraction of 12% is prepared using the second monomer shown in Formula IV and THF, and the silicon-based material is mixed with the monomer solution and then spray-dried to obtain the negative electrode active material.
[0127] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0128] Comparative Example 4
[0129] This comparative example provides a lithium ion battery. Compared with Example 1, the difference in structure is that the material composition of the coating layer of the negative electrode active material is different, the first monomer contained in the coating layer is as shown in Formula X, and the second monomer is as shown in Formula XI;
[0130]
[0131] The negative electrode active material used in this comparative example is prepared by the following steps:
[0132] S1. The first monomer and the second monomer are mixed in a molar ratio of 1:1 and dissolved in THF to prepare a monomer solution with a mass fraction of 12%;
[0133] S2. The silicon-based material was added to the monomer solution and stirred at 50°C for 7 hours to obtain a mixed solution, and the mixed solution was spray-dried to form a coating layer with a thickness of 70 nm on the surface of the silicon-based material to obtain a negative electrode active material with a particle size D50 of 6 μm.
[0134] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0135] Test Case
[0136] 1. Participants
[0137] In this test example, the lithium ion batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were used as test objects to conduct relevant performance tests.
[0138] 2. Test content
[0139] (1) First Coulomb efficiency
[0140] At 25°C, the lithium-ion battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C and allowed to stand for 10 minutes. Then, the lithium-ion battery was discharged to 2.5V at a constant current rate of 0.33C and allowed to stand for 10 minutes. The first coulombic efficiency of the lithium-ion battery was calculated.
[0141] First coulombic efficiency (%) = total capacity of the lithium-ion battery discharged at 0.33C for the first time / total capacity of the lithium-ion battery charged at 0.33C for the first time × 100%.
[0142] (2) Capacity retention rate after 1200 cycles at 1C / 1C at room temperature
[0143] At 25°C, the lithium-ion battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium-ion battery is discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This is considered one charge and discharge cycle. The lithium-ion battery is charged and discharged for 1200 cycles according to the above method, and the capacity retention rate of the lithium-ion battery after 1200 cycles of charge and discharge at 1C / 1C is calculated.
[0144] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0145] (3) Room temperature 6C rate performance - constant current charging ratio
[0146] At 25°C, the lithium battery was discharged at a constant current rate of 1C to 2.5V and allowed to stand for 10 minutes. Then, the lithium battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C and allowed to stand for 10 minutes. The 6C constant current charging capacity Q1, the 6C constant current and constant voltage charging total capacity Q2 and the highest temperature during the fast charging process (i.e., the highest temperature of 6C rate charging) of the lithium battery were recorded. The 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = 6C constant current charging capacity Q1 / 6C constant current and constant voltage charging total capacity Q2 × 100%, wherein, the constant current and constant voltage charging total capacity Q2 = constant current charging capacity + constant voltage charging capacity.
[0147] (4) 1C / 10C discharge capacity retention rate at room temperature
[0148] At 25°C, the divided lithium-ion battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C. After standing for 10 minutes, the lithium-ion battery is discharged to 2.5V at a constant current rate of 1C, and its discharge capacity Q is recorded. 1C As the initial discharge capacity; then at 25 ° C, the lithium-ion battery is charged to 4.2V at a constant current and constant voltage rate of 1C, the cut-off current is 0.05C, and it is left to stand for 10 minutes. Then, the fully charged lithium-ion battery is discharged to 2.5V at a constant current rate of 10C, and its discharge capacity Q is recorded. 10C ; Calculate the discharge capacity retention rate of lithium-ion batteries at 1C / 10C rate according to the following formula: Discharge capacity retention rate (%) = discharge capacity Q at 10C rate 10C / Discharge capacity at 1C rate Q 1C ×100%.
[0149] 3. Experimental results
[0150] Table 1 Relevant performance test results of lithium-ion batteries
[0151]
[0152] The relevant performance test results of the lithium ion batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 4 are shown in Table 1.
[0153] The negative electrode active material used in the lithium ion battery provided in Comparative Example 1 is a silicon-carbon material without a coating layer, while the negative electrode active material used in the lithium ion batteries provided in Examples 1 to 12 is obtained by coating a silicon-based material with a copolymer formed by a copolymerization reaction of a first monomer shown in Formula I and a second monomer shown in Formula II. The test results show that the first coulomb efficiency, the capacity retention rate of 1C / 1C cycle 1200 cycles at room temperature, the constant current charging ratio of 6C rate charging, and the discharge capacity retention rate of 1C / 10C at room temperature of the lithium ion batteries provided in Examples 1 to 12 are significantly higher than those in Comparative Example 1. The above results can be It is explained that the silicon-based material is coated with a copolymer formed by a copolymerization reaction of a first monomer represented by formula I and a second monomer represented by formula II. The coating layer can play a good buffering role on the volume expansion of the silicon-based material during the charging and discharging process, so that the negative electrode active material is not easy to rupture during the expansion process, thereby improving the cycle life and cycle capacity retention rate of the lithium-ion battery using the negative electrode active material during actual use, and the coating layer can improve the conductivity of the negative electrode active material to a certain extent, thereby improving the rate performance of the negative electrode active material, so that the lithium-ion battery using it has excellent fast charging performance.
[0154] By comparing the test results of Examples 1, 4, 5, 6, 7, and 8, it can be shown that compared with the first monomer and the second monomer of other structures, the negative electrode active material obtained by coating the silicon-based material with a copolymer formed by the copolymerization reaction of the first monomer shown in Formula III and the second monomer shown in Formula IV in Example 1 has better cycle performance and rate performance.
[0155] By comparing the test results of Examples 1, 9 and 10, it can be shown that the negative electrode active material obtained by coating the silicon-based material with a copolymer having a number average molecular weight in the range of 4000 to 50000 has better cycle performance and rate performance.
[0156] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material includes a silicon-based material and a coating layer disposed on the surface of the silicon-based material, wherein the coating layer contains a copolymer, and the copolymer includes a first monomer as shown in Formula I and a second monomer as shown in Formula II; The X and Y independently contain at least one of an aryl group and an alkenyl group; The Z is selected from one of —Cl, —Br, and —I.
2. The negative electrode active material according to claim 1, characterized in that: The structure of the first monomer is shown in Formula III, and the structure of the second monomer is shown in Formula IV; 3. The negative electrode active material according to claim 1, characterized in that: The number average molecular weight of the copolymer is 4,000 to 50,000.
4. The negative electrode active material according to claim 1, characterized in that: The molar ratio of the first monomer to the second monomer is 1-1.2:
1.
5. The negative electrode active material according to claim 1, characterized in that: The coating layer accounts for 2-8% by mass of the negative electrode active material, and / or the coating layer has a thickness of 10-130 nm.
6. The negative electrode active material according to claim 1, characterized in that: The particle size D50 of the negative electrode active material is 4 to 9 μm, and / or the specific surface area of the negative electrode active material is 1 to 8 m 2 / g.
7. The method for preparing the negative electrode active material according to claim 1, characterized in that: The following steps are involved: S1. copolymerizing the first monomer and the second monomer to obtain the copolymer; S2. preparing a copolymer solution using the copolymer; S3. Applying the copolymer solution to the surface of the silicon-based material, and drying the copolymer solution on the surface of the silicon-based material to form the coating layer on the surface of the silicon-based material.
8. The method for preparing the negative electrode active material according to claim 7, characterized in that: In S1, the copolymer is prepared by the following steps: S1-1. The first monomer, the second monomer, a base and a catalyst are mixed and heated under reflux under an inert gas atmosphere for 5 to 12 hours to obtain a prepolymer; S1-2. The prepolymer is mixed with an organic solvent and an initiator, and the mixture is reacted in an inert gas atmosphere at 40 to 100° C. for 3 to 12 hours to obtain the copolymer.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating disposed on the surface of the negative electrode current collector, wherein the negative electrode active coating contains the negative electrode active material according to any one of claims 1 to 6 or a negative electrode active material prepared by the method for preparing the negative electrode active material according to any one of claims 7 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Composite silicon-based negative electrode material and battery using same
CN118263425A
Silicon-based negative electrode with stable interface, preparation method of silicon-based negative electrode and sulfide solid-state battery
CN118712336A
Negative electrode active material for lithium ion secondary battery and manufacturing method for the same
JP2016189294A